EMC10 (Endoplasmic Reticulum Membrane Protein Complex Subunit 10) Is a Bone Marrow–Derived Angiogenic Growth Factor Promoting Tissue Repair After Myocardial Infarction. Issue 19 (7th November 2017) - Reboll, Marc R.; Korf-Klingebiel, Mortimer; Klede, Stefanie; Polten, Felix; Brinkmann, Eva; Reimann, Ines; Schönfeld, Hans-Joachim; Bobadilla, Maria; Faix, Jan; Kensah, George; Gruh, Ina; Klintschar, Michael; et al.
Abstract : Background: Clinical trials of bone marrow cell–based therapies after acute myocardial infarction (MI) have produced mostly neutral results. Treatment with specific bone marrow cell–derived secreted proteins may provide an alternative biological approach to improving tissue repair and heart function after MI. We recently performed a bioinformatic secretome analysis in bone marrow cells from patients with acute MI and discovered a poorly characterized secreted protein, EMC10 (endoplasmic reticulum membrane protein complex subunit 10), showing activity in an angiogenic screen. Methods: We investigated the angiogenic potential of EMC10 and its mouse homolog (Emc10) in cultured endothelial cells and infarcted heart explants. We defined the cellular sources and function of Emc10 after MI using wild-type, Emc10 -deficient, and Emc10 bone marrow–chimeric mice subjected to transient coronary artery ligation. Furthermore, we explored the therapeutic potential of recombinant Emc10 delivered by osmotic minipumps after MI in heart failure–prone FVB/N mice. Results: Emc10 signaled through small GTPases, p21-activated kinase, and the p38 mitogen-activated protein kinase (MAPK)–MAPK-activated protein kinase 2 (MK2) pathway to promote actin polymerization and endothelial cell migration. Confirming the importance of these signaling events in the context of acute MI, Emc10 stimulated endothelial cell outgrowth from infarcted mouse heart explants via p38 MAPK-MK2. Emc10 protein abundance was increased in the infarcted region of the left ventricle and in the circulation of wild-type mice after MI. Emc10 expression was also increased in left ventricular tissue samples from patients with acute MI. Bone marrow–derived monocytes and macrophages were the predominant sources of Emc10 in the infarcted murine heart. Emc10 KO mice showed no cardiovascular phenotype at baseline. After MI, however, capillarization of the infarct border zone was impaired in KO mice, and the animals developed larger infarct scars and more pronounced left ventricular remodeling compared with wild-type mice. Transplanting KO mice with wild-type bone marrow cells rescued the angiogenic defect and ameliorated left ventricular remodeling. Treating FVB/N mice with recombinant Emc10 enhanced infarct border-zone capillarization and exerted a sustained beneficial effect on left ventricular remodeling. Conclusions: We have identified Emc10 as a previously unknown angiogenic growth factor that is produced by bone marrow–derived monocytes and macrophages as part of an endogenous adaptive response that can be enhanced therapeutically to repair the heart after MI. Abstract : Supplemental Digital Content is available in the text.